2015
DOI: 10.1108/lodj-01-2014-0006
|View full text |Cite
|
Sign up to set email alerts
|

Can socially responsible leaders drive Chinese firm performance?

Abstract: Purpose – The relationship between socially responsible leaders, the key driver of corporate social responsibility (CSR) practices, and organizational financial performance is a salient issue in the global context for both CSR scholars and practitioners. The purpose of this paper is to provide much-needed insights into the interplay of responsible leadership, CSR practices, and organizational outcomes. Design/methodology/approach – It an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 36 publications
2
45
0
1
Order By: Relevance
“…This argument is consistent with the view of other scholars who described mixed evidence in the relationship, but most studies were found to show positive relationship [62]. While some studies found CSR as an increaser of business performance [26,41,42], other scholars documented negative [63] or no relationship [54] between the CSR practices of an organization and its performance. Even though scholars found mixed results of correlation between social responsibility and financial performance, society still desires a firm to implement good social responsibility and environmental management practices [64].…”
Section: Environment As Moderatorsupporting
confidence: 88%
See 1 more Smart Citation
“…This argument is consistent with the view of other scholars who described mixed evidence in the relationship, but most studies were found to show positive relationship [62]. While some studies found CSR as an increaser of business performance [26,41,42], other scholars documented negative [63] or no relationship [54] between the CSR practices of an organization and its performance. Even though scholars found mixed results of correlation between social responsibility and financial performance, society still desires a firm to implement good social responsibility and environmental management practices [64].…”
Section: Environment As Moderatorsupporting
confidence: 88%
“…Several scholars found that CSR activities have a significant effect on business performance [41,42]. Business performance covers the external performance of an organization based on economic valuation as well as internal performance outcomes that are associated with operational efficiency and effectiveness [43].…”
Section: Corporate Social Responsibility (Csr) and Firm Performancementioning
confidence: 99%
“…Responsible leaders have the supervisory power to encourage and support employees to engage in pro-environmental activities, including recycling and reducing pollution (Afsar et al, 2016;Robertson & Barling, 2013). In addition, responsible leaders value organizational sustainability, indicating they are not only concerned about financial performance but also consider the sustainability of the environment and help to deliver on these values (Doh & Quigley, 2014;Miska et al, 2014;S. Wang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Angus-Leppan, Metcalf, and Benn (2010) suggest that transformation leadership is needed to formulate and implement CSR policies successfully. Transformational leaders tend to use idealized and inspirational motivation to arouse followers to accept and perform on leader's vision and collective objectives (B. M. Bass, 1985;Grojean, Resick, Dickson, & Smith, 2004;Wang, Huang, Gao, Ansett, & Xu, 2015) Second, transformational leaders are intellectually stimulating and encouraging followers to challenge the status quo so that they can approach complex situation in more innovative ways (B. M. Bass, 1997;Jones Christensen, Mackey, & Whetten, 2014). Transformational leaders scan the environmental tasks and understand how stakeholders' needs be synchronized.…”
Section: The Moderating Role Of Transformational Leadershipmentioning
confidence: 99%